HOW DO TEACHERS COPE WITH BLENDED LEARNING? A MULTIPLE CASE STUDY AT HIGH SCHOOLS IN LOMBOK – WEST NUSA TENGGARA - Bq. Nurul Alya; Henny Soepriyanti; Untung Waluyo (Program Studi Pendidikan Bahasa Inggris, 2023)
Following the policy of New Normal in the post Covid-19 Pandemic, the Indonesian government has begun introducing blended learning activities. Because of this policy, teachers have been encouraged to establish a plan for using blended learning that is aligned with the learning interests of the students. Therefore, the emphasis of this research was on the technique that the teacher and school administration employed in order to improve the English language education system after the COVID-19 outbreak. The purpose of this study was to provide a description of the approach taken by English teachers following the establishment of the new normal in the time period following the Covid-19 Pandemic. A descriptive qualitative methodology was utilized for this investigation. Participants in the study were English teachers working at SMAX, SMAY, and SMAZ schools located in Mataram City. In this particular study, the methods of data collecting that were utilized were observation, interviews, and documentation. According to the findings of the study, educators devised a variety of instructional methods in order to deal with the challenges posed by blended learning modes, which placed equal emphasis on synchronous and asynchronous learning. The findings of the research answered well the guiding research questions. The study concludes that teachers encountered significant challenges when utilizing asynchronous learning mode. The challenges arose as a consequence of insufficient student involvement as well as inadequate assistance for internet connection. As a result of the decreased amount of time allotted for learning, it was discovered that certain teachers struggle with managing their time effectively.